The association between lipid profile and bone mineral density in subjects with ankylosing spondylitis - Sargın, Betül; Gürer, Gülcan; Öztürk, Hakan (The European Research Journal, 2019)
Objective: This study aims to investigate the relationship between serum lipids and bone mineral density in ankylosing spondylitis patients.Methods: A total of 94 ankylosing spondylitis patients fulfilling the 1984 Modified New York Criteria who had serum lipid levels and bone mineral density scores in medical records were included in this study. These patients treated with nonsteroid antiinflammatory drugs. Their files were examined in detail. Later demographic and laboratory features were recorded to the research form. Dual-energy X-ray absorptiometry was used to assess bone mineral density in two bone sites of femur (neck, intertrochanteric zone and trochanter) and spinal lumbar vertebras (Lumbar 1-Lumbar 4).Results: Significant and positive correlation was found between high density lipoprotein and femoral neck bone mineral density (r = 0.356, p = 0.021) in osteopenic group and in osteoporotic group (r = 0.005, p = 0.040). Conclusion: According to our study significant and positive correlations are found between high density lipoprotein and femoral neck bone mineral density in osteopenic and osteoporotic group. However, we believe that more studies are needed about this research.